RANCANGAN ALAT UJI BEBAN DINAMIK UNTUK SISTEM SAMBUNGAN KONSTRUKSI BAMBU - Suwarsono . (Jurnal Gamma, 2009)
Bamboo construction is widely used by Indonesian people, especially in rural areas, to buildinghouses, bridges, fences, etc., because it is cheap and quick to grow (bamboo can be harvested at theage of 3-5 years, compared with wood 30-50 yrs.). So much bamboo growing in the yard behind thehouse and in the field as a backup. Today’s technology can process the bamboo into bamboo laminate,so that could be used for floors, skateboard, furniture furniture until frame (frame) bike sport.Bamboo has the mechanical properties, particularly in the direction of fibers, which are quitegood. For the construction of bamboo has a weakness in the joint system. At the time of construction,connection systems rely solely on the strength of friction from the rope. Lately, research on bambooswitching system design is very diverse, but very little literature that reveal the mechanical properties(tensile strength, bending, shear, fracture and dynamic) bamboo joint system, thus avoiding thearchitects design, construction using bamboo.This study is the beginning, of a series of research on bamboo and bamboo test connection forthe dynamic character for construction. This initial research to produce a model of dynamic loadtesting tools for the construction of bamboo, for a maximum load of 5 kg, for further necessaryresearch for the design of advanced test equipment dynamic load 5000 kg and a test of the dynamiccharacter of the bamboo joint, resulting in a dynamic test data connections bamboo, thus the designerhas refrensi about the mechanical properties of bamboo and bamboo connections, which in turn canuse the software as a CAD-CAE design tool bamboo construction.